"Unintended effects": A theorem for complex systems. Issue 2 (29th September 2014) - Usó‐Doménech, J.L.; Nescolarde‐Selva, J.; Lloret‐Climent, M.
Abstract : Unintended effects are well known to economists and sociologists and their consequences may be devastating. The main objective of this article is to formulate a mathematical theorem, based on Gödel's famous incompleteness theorem, in which it is shown, that from the moment deontical modalities (prohibition, obligation, permission, and faculty) are introduced into the social system, responses are allowed by the system that are not produced, however, prohibited responses or unintended effects may occur. © 2014 Wiley Periodicals, Inc. Complexity 21: 342–354, 2015